ANALISIS KANDUNGAN KAFEIN DALAM KOPI SUMATERA DAN KOPI FLORES DENGAN VARIASI SIKLUS MENGGUNAKAN SPEKTROFOTOMETER UV-VIS - Nadhirah -; Alimuddin -; Chairul Saleh (JURNAL KIMIA MULAWARMAN, 2015)
The research about analysis of caffeine content on coffee Sumatera and coffee Flores with cycle variations using spectrophotometer UV-Vis has been done. Coffee extract obtained through soxhletation with ethanol 96% and variation cycles used is 3, 6, 9, 12 and 15. The extract obtained is dissolved in ethanol 96% and tested with spectrophotometer UV-Vis at a wavelength of 272 nm. The result obtained in this research is the caffeine content in coffee Sumatera for 3, 6, 9, 12, 15 cycles consecutive are 0.582 mg/L; 0.986 mg/L; 1.315 mg/L; 2.143 mg/L and 2.918 mg/L. While the caffeine content obtained coffee Flores for 3, 6, 9, 12, 15 cycles consecutive are 0.465 mg/L; 0.599 mg/L; 0.728 mg/L; 1.186 mg/L and 1.653 mg/L.Keywords : Coffee Sumatera, Coffee Flores, Ethanol 96%, Soxhletation, Caffeine, Spectrophotometer UV-Vis